Neoplatonic demons and angels. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2018)
Neoplatonic Demons and Angels is a collection of eleven studies which examine, in chronological order, the place reserved for angels and demons not only by the main Neoplatonic philosophers (Plotinus, Porphyry, Iamblichus, and Proclus), but also in Gnosticism, the Chaldaean Oracles, Christian Neoplatonism, especially by Pseudo-Dionysius the Areopagite. This volume originates from a panel held at the 2014 ISNS meeting in Lisbon, but is supplemented by a number of invited papers.